2021
DOI: 10.3389/fimmu.2020.608134
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in HLA B27 Anterior Uveitis

Abstract: There has been steady progress in understanding the pathogenesis, clinical features, and effective treatment of acute anterior uveitis (AU) over the past 5 years. Large gene wide association studies have confirmed that AU is a polygenic disease, with overlaps with the seronegative arthropathies and inflammatory bowel diseases, associations that have been repeatedly confirmed in clinical studies. The role of the microbiome in AU has received increased research attention, with recent evidence indicating that hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 85 publications
0
27
0
Order By: Relevance
“…One extension of the present study will be to define the responses of stroma 1 and stroma 2 cells to inflammation. Iris inflammation (iritis) is one component of anterior segment uveitis, a common autoimmune condition ( Martin et al, 2002 ; Artornsombudh et al, 2014 ; Wakefield et al, 2020 ). Work in a variety of disease contexts has shown that stromal cells change their patterns of gene expression in response to inflammation and that they can epigenetically ‘remember’ prior bouts of inflammation ( Neumann et al, 2010 ; Crowley et al, 2018 ; Mizoguchi et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…One extension of the present study will be to define the responses of stroma 1 and stroma 2 cells to inflammation. Iris inflammation (iritis) is one component of anterior segment uveitis, a common autoimmune condition ( Martin et al, 2002 ; Artornsombudh et al, 2014 ; Wakefield et al, 2020 ). Work in a variety of disease contexts has shown that stromal cells change their patterns of gene expression in response to inflammation and that they can epigenetically ‘remember’ prior bouts of inflammation ( Neumann et al, 2010 ; Crowley et al, 2018 ; Mizoguchi et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact pathogenesis of AU remains unclear, largescale genome wide association studies have confirmed that AU is a polygenic disease, with overlaps with the seronegative arthropathies and inflammatory bowel diseases, associations that have been repeatedly confirmed in clinical studies (Wakefield et al, 2020). Some evidence has proven that epigenetic modifications are involved in the regulation of AU development, such as microRNAs.…”
Section: Epigenetic Modifications and Anterior Uveitismentioning
confidence: 99%
“…In severe forms of acute AU (AAU), hypopyon and fibrin can be visualized as a white and dense clot in the anterior chamber ( Agrawal et al, 2010 ). In addition, approximately 50% of all patients with acute AU (AAU) are human leukocyte antigen B27 (HLA B27) positive ( Wakefield et al, 2020 ). Some authors speculate on the prognosis of HLA-B27-related AAU, reporting a higher frequency of recurrence and a worse outcome than HLA-B27-negative AAU ( Rothova et al, 1987 ; Power et al, 1998 ).…”
Section: Epigenetic Modifications In Different Types Of Uveitismentioning
confidence: 99%
“…HLA-B27 is associated with the development of common inflammatory rheumatic diseases such as the spondyloarthritides (SPA), ankylosing spondylitis (AS), and reactive arthritis [102]. HLA-B27 is also associated with inflammatory eye disease, anterior uveitis [103]. HLA-B27 is devoid of β2m and HLA-II in a transgenic mouse model that develops arthritis.…”
Section: Face-3 Of Hla-b27mentioning
confidence: 99%